Cyber Law Policy Development: Indonesia's Response to International Cybercrime Threats - Rusydi, Muhammad Taufik (PT. Riset Press International, 2025)
The rapid development of information technology has driven the growth of the digital economy but also increased the threat of cross-border cybercrime. In Indonesia, cyber law regulation still faces challenges, both in terms of legal substance, institutions, and implementation of law enforcement. This article aims to explore the strengthening of cyber law policy in Indonesia to face global challenges in cybercrime. This article identifies various weaknesses in existing policies using a juridical-normative research method and a descriptive-analytical approach. It recommends strengthening regulatory harmonization, increasing law enforcement capacity, and international collaboration. The results of the study indicate that Indonesia's cyber law framework needs to be updated to be more adaptive to technological developments and global threats. In addition, integrating national law and international policy is a major highlight in increasing the effectiveness of controlling cybercrime. This article makes an important contribution to the development of responsive and relevant cyber law in facing the challenges of the digital era.